THE IMAGE OF THE HERO IN EIGHTEENTH–NINETEENTH-CENTURY LITERATURE: EVOLUTION AND TYPOLOGY (Journal of Multidisciplinary Sciences and Innovations, 2025)
The study of the image of the hero in 18th–19th century Russian literature is relevant as it allows tracing the evolution of artistic consciousness and changes in the perceptions of personality and social values. The analysis of hero typology reflects cultural and historical transformations and demonstrates how literature shapes and records the moral, psychological, and philosophical guidelines of its time. Understanding the development of the hero’s image contributes to a deeper comprehension of the interaction between the individual and society, as well as the mechanisms of artistic representation of a character’s inner world.